What makes working memory traces stable over time?. Issue 1 (9th May 2018) - Jarjat, Gabriel; Hoareau, Violette; Plancher, Gaën; Hot, Pascal; Lemaire, Benoît; Portrat, Sophie
Abstract: Understanding the factors that make working memory (WM) traces stable over time is important because WM is the keystone of general cognitive achievement. Two views of attentional WM maintenance have been suggested to account for the long‐term retention of WM information. First, the distractors in a WM task are thought to foster the creation of episodic memory cues through covert retrieval. Second, the cognitive load (CL) of the distractors is thought to vary long‐term memory instantiation. In this study, we propose an additional parsimonious perspective: the total time during which each trace is under the control of attention in WM is the key to long‐term retention. Participants performed a complex span task in which the CL and number of distractors were orthogonally manipulated, and thereafter the participants performed a delayed recall test. Similar to previous findings, the results showed effects of the number of distractors and of CL on delayed recall. Our results went further, however, by showing a non‐linear relationship between delayed recall performance and the free time accumulated between encoding and immediate recall. The role of time in episodic memory performance and the underlying WM maintenance mechanism are discussed. Abstract : Two views of working memory (WM) maintenance may account for long‐term retention: (1) distractors foster the creation of episodic memory cues through covert retrieval; and (2) the cognitive load of the distractors vary long‐term memory instantiation. Here, we propose that the total time during which each trace is under the control of attention in WM is key to long‐term retention.